Hereditary angioedema diagnosis: Reflecting on the past, envisioning the future - Anete S. Grumach, MD, PhD; Marc A. Riedl, MD, MS; Lei Cheng, MD, PhD; Siddharth Jain, MD; Daniel Nova Estepan, PharmD, RPh; Andrea Zanichelli, MD, PhD (World Allergy Organization Journal)
Individuals with hereditary angioedema (HAE), a rare disease most frequently associated with deficiency (HAE-C1INH-Type1) or dysfunction (HAE-C1INH-Type2) of C1 inhibitor (C1INH), continue to experience frequent misdiagnoses and long delays in diagnosis, preventing appropriate management strategies and placing the patients at continued risk of inappropriate management of painful, debilitating, and potentially fatal swelling attacks. Physician education to increase HAE awareness is important to initiate diagnostic testing for patients who may be at risk of HAE. Standard tests for diagnosing HAE-C1INH-Type1 and HAE-C1INH-Type2 include measurements of antigenic C4 level, antigenic C1INH level, and C1INH function; in contrast, known subtypes of HAE due to normal C1INH can only be confirmed through genetic testing. Current diagnostic tests have certain limitations related to sample handling, storage, and transportation; concerns about the sensitivity and specificity of current assays have also been reported. Furthermore, the accessibility of diagnostic testing for HAE is not universal. Therefore, there is a persistent need for robust and accessible diagnostic tools for HAE. In this review, we provide an overview of currently available assays for HAE diagnosis and summarize some of the novel diagnostic tools that may aid in overcoming diagnostic challenges in HAE and supporting the care of patients with HAE.